PERSEPSI MASYARAKAT DESA HUTAN LAHAN BASAH TERHADAP PERUBAHAN FUNGSI CAGAR ALAM MENJADI TAMAN WISATA ALAM - Setia Budi Peran; Zainal Abidin; Badaruddin Badaruddin (Jurnal Hutan Tropis, 2021)
This research aims to analyze the public perceptions to the function change the nature preserve of Pulau Burung becomes the nature tourist park in the Pulau Burung Forest Village. The analysis used in this research is by using a Likert Scale analysis. The research location is housed in the Pulau Burung Village of District Tanah Bumbu. This study uses primary data obtained directly through a questionnaire to the villagers of the District Pulau Burung. Secondary data obtained through the government in the village. The sampling using simple random sampling method, where all members have the same population was selected as a representative sample of the population. To determine the public perception then used the likert scale analysis. The results showed that a high perception of the function change of nature preserve become nature tourist park and it’s management in the Forest Village District of Pulau Burung, seen from three indicators of responses/opinions, knowledge, and attitudes